2018
DOI: 10.1587/transinf.2017edp7177
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Kit-Build Method for Assessment of Learner-Build Map by Comparing with Manual Methods

Abstract: This paper describes an investigation into the validity of an automatic assessment method of the learner-build concept map by comparing it with two well-known manual methods. We have previously proposed the Kit-Build (KB) concept map framework where a learner builds a concept map by using only a provided set of components, known as the set "kit". In this framework, instant and automatic assessment of a learnerbuild concept map has been realized. We call this assessment method the "Kit-Build method" (KB method)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…It is possible to display exactly in which ways the student map differs from the expert map because they are built from the same pieces. This type of automatic diagnosis was found to be reliable when compared to traditional map scoring approaches (Wunnasri et al 2018;Wunnasri et al 2017) and was found to correlate with standard science tests (Yoshida et al 2013). This type of automated measurement has been used to measure changes in interdisciplinary learning during high school (Reiska et al 2018).…”
Section: Computer-based Concept Map Tools and Closed Concept Mapsmentioning
confidence: 98%
“…It is possible to display exactly in which ways the student map differs from the expert map because they are built from the same pieces. This type of automatic diagnosis was found to be reliable when compared to traditional map scoring approaches (Wunnasri et al 2018;Wunnasri et al 2017) and was found to correlate with standard science tests (Yoshida et al 2013). This type of automated measurement has been used to measure changes in interdisciplinary learning during high school (Reiska et al 2018).…”
Section: Computer-based Concept Map Tools and Closed Concept Mapsmentioning
confidence: 98%
“…This method has the same efficiency as the original method for comprehended information in a comprehension test taken just after reading (Funaoi, Ishida, & Hirashima, 2011). The KB-map assessment method is automated, and its validity for evaluating the understanding of learners has been confirmed (Wunnasri, Pailai, Hayashi, & Hirashima, 2018). In addition to the one-on-one comparison, overlapping the learner maps as the representation of the aggregated understanding of learners is possible.…”
Section: Introductionmentioning
confidence: 96%
“…KB map and assessment methods have already been practically used in classrooms in various schools, for example, in science learning in elementary schools [16], [17], geography in junior high schools [18], the learning of English as a second language [19], social science and computer science in university [20], [21]. Even KB map assessment method is an automatic assessment, it was examined the validity for eval-uating learners' understanding [22], [23]. This investigation can suggest that KB map can support learners to express their understanding suitably.…”
Section: Introductionmentioning
confidence: 99%